2022
DOI: 10.1002/pd.6246
|View full text |Cite
|
Sign up to set email alerts
|

Solomon versus selective fetoscopic laser photocoagulation for twin‐twin transfusion syndrome: A systematic review and meta‐analysis

Abstract: This meta-analysis aims to compare the perinatal outcome of twin-twin transfusion syndrome (TTTS) pregnancies undergoing selective versus vascular equator (Solomon) fetoscopic laser photocoagulation (FLP). We performed a systematic search in PubMed and Web of Science from inception up to 25 July 2021. Studies comparing the Solomon and selective techniques of FLP for treatment of TTTS pregnancies were eligible. Random-effects or fixed-effect models were used to pool standardized mean differences (SMD) and log o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…Complications of fetoscopic laser photocoagulation include placental abruption and preterm delivery. In cases of TTTS, placental abruption is more common following laser surgery 25 . In this case series, 3/13 (23%) cases were complicated by placental abruption with subsequent preterm delivery.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Complications of fetoscopic laser photocoagulation include placental abruption and preterm delivery. In cases of TTTS, placental abruption is more common following laser surgery 25 . In this case series, 3/13 (23%) cases were complicated by placental abruption with subsequent preterm delivery.…”
Section: Discussionmentioning
confidence: 63%
“…In cases of TTTS, placental abruption is more common following laser surgery. 25 In this case series, 3/13 (23%) cases were complicated by placental abruption with subsequent preterm delivery. The average gestational age at delivery among all patients was 29w3d, which likely reflects both the complexity of surgery but also the early gestational age at which surgery was performed.…”
Section: Discussionmentioning
confidence: 66%
“…Two meta-analyses comparing selective FLC to the Solomon technique for pregnancies complicated by TTTS have been recently published. 26,27 Both found the Solomon technique to be associated with a lower rate of recurrent TTTS, however, both also demonstrated a significant increase in the rate of placental abruption. One of the meta-analyses by D'Antonio et al 26 demonstrated a higher rate of survival for FLC using the Solomon technique when compared with selective FLC, but they also demonstrated that the Solomon technique was associated with an earlier gestational age at delivery.…”
Section: Management Of Tttsmentioning
confidence: 99%
“…Two meta-analyses comparing selective FLC to the Solomon technique for pregnancies complicated by TTTS have been recently published 26,27 . Both found the Solomon technique to be associated with a lower rate of recurrent TTTS, however, both also demonstrated a significant increase in the rate of placental abruption.…”
Section: Introductionmentioning
confidence: 99%